Upaya Guru Dalam Meningkatkan Hasil Belajar Pendidikan Agama Islam di Sekolah Dasar - Novia Hardiyanti, dkk. (Program Studi Pendidikan Agama Islam, 2020)
The present study aimed at finding out the efforts made by teachers to improve the outcomes of Islamic education (PAI) learning undertaken by IV grade students at SDN 156 in Bangun Jaya village, Rejang Lebong regency. This study used a qualitative approach, and the data were collected using observation and interview techniques. After data collection, analyses were carried out with the following stages: selecting data, presenting data, and drawing conclusion. This study concluded that the efforts made by teachers in improving students’ learning outcomes of PAI included: asking the principal to add learning hours outside PAI teaching hours; communicating with students’ parents to remind their children of rehearsing lessons at home; making evaluations before and after the lessons; choosing approaches or methods that appealed to students; making use of learning media to make it easier to explain the materials so that the materials were easily understood by students; and using the reward and punishment methods. The description of PAI learning outcomes for the fourth grade students was quite good because all students’ values in the school year of 2019-2020 could be seen from the results of their semester which had reached the specified KKM standard.